Tingkat Persaingan Eksportir Utama Lada Dunia - Jannah, Eka Miftakhul; Nurmalina, Rita; Asmarantaka, Ratna Winandi (Jurnal Agro Industri Perkebunan, 2019)
Indonesia's pepper growth rate tends to decrease compared to the growth rate of world pepper demand. This is due to the decline in production in Indonesia in recent years. This has an impact on the amount offered by Indonesia to meet the needs of the world. Indonesia's inability to compete with other countries makes Indonesia's position in taking on the growth of the world's hopes can be used by other countries. This situation can change Indonesia's position and competitiveness in trade on the international market. This study aims to analyze the level of competition between countries by using Revealed Comparative Auntungan (RCA and Dynamics Revealed Comparative Advantage (DRCA). The results of the study show that during the 2011-2013 period the highest increase in competitiveness between countries during the other period was an increase Significant exports to the countries of Brazil, India and Pakistan which increased on the value of RCA. Delaying in the 2011-2013 and 2014-2016 periods was related to increasing countries increasing exports such as Indonesia, Brazil and India. Position of Indonesia in 2016 Enlarging free markets greater than the results of world exports, Indonesia must increase the country's competitiveness.